Philosophical analysis of the psychological effects of informatization and computerization - Сухомлин, Р.Г. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2012)
The article philosophical analysis of the psychological effects of informatization and computerization as a part of the Information Society.